The Influence of Power on Decisions Constitutional Court (MK) Concerning the Age Limit for Vice Presidential Candidates in 2023 - Azhari M. Hadi Putra; Doni Hendrik; Nilma Suryani (Jurnal Hukum Prasada, 2024)
There are so many irregularities in the Constitutional Court's decision Number 90/PUU-XXI/2023 regarding the age limit for presidential candidates. The author suspects that there is interference from the ruling elite who have an interest in maintaining the current power status quo. The analysis of this writing will be dissected using an understanding of elite theory and patterns White Collars Criminal. Jokowi and the current ruling elite group have an interest in remaining is within the scope of power. Meanwhile, regulations to continue being in power no longer provide space. Therefore, Jokowi and his group need to extend their hand in the circle of power in the future after he steps down, through legal manipulation so that his son can advance as a state official. Jokowi's efforts together with other elite groups behind this political attitude that is contrary to democratic values, is suspected to be an inevitability that can arise from those in power. The state government's grip on power, which has been going on for almost a decade, is starting to show that it is mentally and psychologically unprepared for its end. This pattern of efforts has led to a series of irregularities in political and legal events over the past year or so. In the end, it all boils down to Gibran's official step forward as vice presidential candidate. This article was written using a qualitative approach with descriptive analysis methods. The data collection technique used is literature study, which is related to theoretical studies and several references.